2011
DOI: 10.17221/34/2010-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Expression of resistance to Ramularia leaf spot in winter barley cultivars grown in conditions of the Czech Republic

Abstract: Abstract:The fungus Ramularia collo-cygni is increasingly important as the causal agent of Ramularia leaf spot (RLS), a novel leaf spot disease of barley. The work aimed to identify gene resources suitable for developing new breeding lines of winter barley with improved resistance. During the first experimental period (2001)(2002)(2003)(2004)(2005), RLS incidence was monitored in 711 cultivars and advanced breeding lines. Differences were detected in the intensity of symptomatic expression, but no material sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, for RLS development a combination of abiotic factors as well as the host GS appear to be crucial [66,68]. In the Czech Republic, lower disease symptoms were observed when lower rainfall and higher temperatures occurred post heading (GS 59) [69]. Similar observations were made in Germany, where lower RLS severity was recorded in the warmer and drier years of 2017 and 2019 [70].…”
Section: Effect Of Host Heat Stress On Dothideomycete-induced Diseasesmentioning
confidence: 54%
“…However, for RLS development a combination of abiotic factors as well as the host GS appear to be crucial [66,68]. In the Czech Republic, lower disease symptoms were observed when lower rainfall and higher temperatures occurred post heading (GS 59) [69]. Similar observations were made in Germany, where lower RLS severity was recorded in the warmer and drier years of 2017 and 2019 [70].…”
Section: Effect Of Host Heat Stress On Dothideomycete-induced Diseasesmentioning
confidence: 54%
“…The interaction between the fungus and host plant is now elucidated at the molecular level (Lemcke et al, 2021;Sjokvist et al, 2019). Marik et al (2011) found that stronger symptomatic expression was positively affected by a higher number of rainy days in the three weeks post-flowering. These authors also reported that higher temperatures and lower rainfall post-flowering reduced disease levels in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…While this study confirms the presence of R. collo-cygni in Australia, assessment of samples from a small number of fields limited the ability to describe the incidence and distribution across barley growing regions. The bioRxiv distribution of R. collo-cygni in Australia may be affected by environmental conditions, as RLS is reported to be more severe in cool, wet environments(Dussart et al 2020;Hoheneder et al 2021b;Mařík et al 2011;McGrann and Brown 2018) compared to drier conditions, however distinct disease responses to environmental factors require further investigation.…”
mentioning
confidence: 99%